Complexes of platinum and palladium with beta-diketones and DMSO: Synthesis, characterization, molecular modeling, and biological studies - Couto Almeida, J. do; Marzano, I. M.; Silva de Paula, F. C.; Pivatto, M.; Lopes, N. P.; Souza, P. C. de [UNESP]; Pavan, Fernando Rogério [UNESP]; Formiga, A. L. B.; Pereira-Maia, B. C.; Guerra, W. (Elsevier B.V., 2014)
This work reports on the synthesis and characterization of new complexes of the type MCl(L)DMSO], where L = 4,4,4-trifluoro-1-phenyl-1,3-butanedione (HTPB) or 4,4,4-trifluoro-1-(2-thienyl)-1,3-butanedione (HTTA) and M = Pt2+ or Pd2+. These complexes were characterized by elemental analyses, conductivity measurements, FT-IR, UV-Vis, high-resolution mass spectra (HRESIMS) and TG/DTA. In the complexes, the metallic ions bind to beta-diketone via the oxygen atoms and to DMSO molecule via sulfur atom. The structures of complexes were optimized and theoretical data showed good agreement with the experimental results. The cytotoxic activity of the compounds was evaluated in a chronic myelogenous leukemia cell line. The platinum complexes were more cytotoxic than the free ligands and carboplatin and are promising candidates for further investigations. As example, the compound [PtCl(TPB)(DMSO)] inhibits the growth of K562 cells with an IC50 value equal to 2.5 mu M, Furthermore, microbiological assays against Mycobacterium tuberculosis showed that all complexes exhibit low cytotoxicity against this bacterial strain while the free ligands exhibited MIC values of approximately 10 mu g mL(-1). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Metal complexes; Molecular modeling; beta-Diketones; Mycobacterium tuberculosis; Cytotoxic activity